Implementation of Wordwall-Based Learning Media in Improving Students' Understanding of Social Studies Learning of Human Materials, Places, and Environments at ICC Muar Malaysia - Zahroh Firdausi; Sigit Dwi Laksana; Anip Dwi Saputro; Navin Ruditiyawan Bin Mohd Mohan (Sekolah Tinggi Ilmu Al-Qur'an (SIQ) Amuntai Kalimantan Selatan, 2026)
This research aims to improve students' understanding of social studies learning of human materials, places, and environments through the application of Wordwall learning media at ICC Muar, Malaysia. The background of the research departs from the low understanding of students and the limited access to education of Indonesian Migrant Workers. The study used the Kemmis and McTaggart model Class Action Research (PTK) method which was carried out in two cycles, involving 27 students. Data was collected through observation, learning outcome tests, interviews, and documentation, then analyzed using the Miles, Huberman, and Saldana models. The results showed a significant increase in student motivation, activeness, and comprehension after the use of Wordwall. The percentage of learning completeness increased from 44.4% in the pre-cycle to 51.85% in Cycle I, and reached 81.48% in Cycle II. The average score of students rose from 58.5 to 84.8. Teacher and student activities also increased from the fair to excellent category. The research concludes that Wordwall is effective as an interactive learning medium that is able to improve student understanding and is suitable for sustainable application in social studies learning.